1990
DOI: 10.1161/01.hyp.15.2_suppl.i93
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal effects of dexamethasone on vasodilatory responses to arachidonic acid and prostanoids in the isolated perfused rabbit kidney.

Abstract: We reported that dexamethasone treatment of rabbits causes a reduction in renal vasoconstrictor responses to prostaglandin F^ and U46619, an agonist at the thromboxane-endoperoxide receptor, but not to phenylephrine. The purpose of this study was to examine if dexamethasone treatment can affect the renal vasodilatory responses to prostacydin (PGIi) and prostaglandin Ej (PGE2) in isolated Krebs-perfused kidneys constricted with phenylephrine. In kidneys from dexamethasone-treated rabbits, the vasodilatory respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Previous studies examining Ang II-dependent hypertension support a role for constrictor prostanoids and have implicated PGH 2 , TxA 2 , or PGF 2α as potential mediators (48,49). Other studies suggest that PGE 2 could also subserve this vasoconstrictor role (16,17,19,50). The present studies now suggest that these constrictor prostanoids may derive from COX1 as opposed to COX2.…”
Section: Figuresupporting
confidence: 65%
“…Previous studies examining Ang II-dependent hypertension support a role for constrictor prostanoids and have implicated PGH 2 , TxA 2 , or PGF 2α as potential mediators (48,49). Other studies suggest that PGE 2 could also subserve this vasoconstrictor role (16,17,19,50). The present studies now suggest that these constrictor prostanoids may derive from COX1 as opposed to COX2.…”
Section: Figuresupporting
confidence: 65%
“…Glucocorticoids increase GFR and alter renal vascular responsiveness to prostaglandins, probably by affecting both cyclooxygenase and cytochrome P-450-dependent AA metabolism as well as by altering "the expression of receptor-mediated contractile responses to eicosanoids" (55, 56) . Sessa & Nasjletti (56) have shown selective attenuation of renal vasoconstrictor responses to U46619, the thromboxane/prostaglandin endoperoxide mimetic, and to PGF2a after dexamethasone treatment of rabbits and have extended these findings to vasodilator prostanoids (55). Prostacyclin and PGErinduced renal vasodilatation were attenuated and converted to vasoconstriction, respec tively, when rabbits were treated with dexamethasone.…”
Section: The Cytochrome P-450 System In the Nephronmentioning
confidence: 94%
“…An adenylate cyclase-dependent mech anism that regulates expression of cytochrome-P-450 isozymes has been described in the adrenal gland (54). Another important consideration relative to the action of adrenal ster oids on renal function, and linked to changes in AA metabolism, is related to effects on GFR and renal blood flow (55). Glucocorticoids increase GFR and alter renal vascular responsiveness to prostaglandins, probably by affecting both cyclooxygenase and cytochrome P-450-dependent AA metabolism as well as by altering "the expression of receptor-mediated contractile responses to eicosanoids" (55, 56) .…”
Section: The Cytochrome P-450 System In the Nephronmentioning
confidence: 99%
“…They demonstrated that allicin is probably the major active ingredient in garlic that gives rise to the vasodilation effect (Ku et al, 2002). Further studies suggested that such effect is brought about by the action of nitric oxide (NO) and stimulatory response of vascular endothelium cells instead of vasodilatory prostanoids such as prostacyclin (PGI 2 ) and prostaglandin E 2 (PGE 2 ) (Lin and Nasjletti, 1991;Sessa et al, 1990).…”
Section: Induction Of Vasorelaxationmentioning
confidence: 99%